Measurement and Analysis of Total Factor Productivity Growth in Modern Variety Potato (Journal of Agriculture & Rural Development, 2010)
The study dealt with the whole scenario of modern variety potato production in Bangladesh covering the period from 1980-81 to 2005-06. The study estimated the extent of shift of production function or the supply curve of modern variety of potato in Bangladesh. The total factor productivity index was estimated using the Tornqvist-Theil index formulation. The growth rate of area, production and yield were found increasing steadily from the year 1980-81. A substantial change has been started from the year 1998-99. The trend of inputs used was found increasing. Almost all the partial as well as the input, output and total factor productivity indices were also found increasing. It may be concluded that for sustaining the present growth of modern variety potato production, the development of new varieties of potato and extensive extension works are needed. Key words: Growth rate, partial factor productivity, total factor productivity, modern variety potato. DOI: 10.3329/jard.v7i1.4423 J Agric Rural Dev 7(1&2), 65-71, June 2009